Development of Ratawi Oil Field, Southern Iraq - Ahmed, Musaab Mahdi; Al–Kubaisi, Manal Shakir (Iraqi Journal of Science, 2018)
Ratawi Field is a promising hydrocarbon bearing structure conforming several reservoirs, and lies northwest of the Basrah city and west of Northern Rumaila Field. Kinetic Analysis referred to that the type of Fold of Ratawi Structure similar to the types which are associated with Salt Structure activity.Geophysical Interpretation referred to the presence of Salt Structure beneath Ratawi Structure. The Isopach Maps shows that the crest thickness is less than the limbs, this characteristics is always due to those of salt structures beneath Ratawi field. Both of Tectonic Movement and Salt Structure play a great role in forming and development of Ratawi Structure.